2018
DOI: 10.3390/molecules23092254
|View full text |Cite
|
Sign up to set email alerts
|

Protection against UVB-Induced Wrinkle Formation in SKH-1 Hairless Mice: Efficacy of Tricin Isolated from Enzyme-Treated Zizania latifolia Extract

Abstract: Tricin, a flavone found mainly in rice bran and sugarcane, has various beneficial effects. It has proven to be a clinically safe and selective potent inhibitor of different cancer cell lines. In this study, we evaluated the efficacy of enzyme-treated Zizania latifolia (ETZL) and its major active compound tricin on skin photoaging in SKH-1 hairless mice. Tricin (0.3 mg/kg) and ETZL (50, 150, and 300 mg/kg) were orally administrated to mice for 14 weeks; no cytotoxicity was observed during the entire experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…Recent animal studies demonstrated the broad-spectrum bioactivities of tricin, ranging from anti-obesity effect in high-fatdiet-induced obese mice [ 33 ] to protection against UVB-induced wrinkle formation [ 34 ]. Nevertheless, the anti-metastatic and/or immunomodulatory effects of tricin in colon cancer model have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recent animal studies demonstrated the broad-spectrum bioactivities of tricin, ranging from anti-obesity effect in high-fatdiet-induced obese mice [ 33 ] to protection against UVB-induced wrinkle formation [ 34 ]. Nevertheless, the anti-metastatic and/or immunomodulatory effects of tricin in colon cancer model have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, limited information is available on wrinkle formation through ROS generation and lysosomal exocytosis by UVA irradiation compared with wrinkle formation by UVB irradiation. In addition to the known antioxidant effects of ZLE [ 38 ], it also showed an antiwrinkle effect on UVB-irradiated HDFs and SKH-1 hairless mice by blocking the MAPK signaling pathway resulting in the inhibition of NF-κB and activator protein-1 (AP-1) activities [ 18 , 19 ]. Both ZLE and tricin treatments showed skin protective effects and helped reduce wrinkle formation in UVA-irradiated human dermal fibroblasts and hairless mice in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The aerial parts of Z. latifolia were purchased from Pureunsan Agricultural Association Corporation (Pocheon, Korea) and ZLE, prepared according to a previously described method [ 18 ], was provided from the BTC Corporation (Sangnok-gu, Ansan, Korea). The concentration of tricin in ZLE was determined by HPLC using an Agilent Infinity 1260 system (Agilent Technologies, Palo Alto, CA, USA), which was measured in our previous study [ 19 ]. The separation of tricin was conducted at 30 °C using a SUPELCO Discovery ® C18 column (4.6 × 250 mm, 5 μm, Merck KGaA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations